Patient-Reported Outcomes Measurement Information System Outcome Measures and Mental Health in Orthopaedic Trauma Patients During Early Recovery. Issue 9 (September 2018) - Vincent, Heather K.; Hagen, Jennifer E.; Zdziarski-Horodyski, Laura A.; Patrick, Matthew; Sadasivan, Kalia K.; Guenther, Robert; Vasilopoulos, Terrie; Sharififar, Sharareh; Horodyski, MaryBeth
Abstract : Objectives: This study explored the relationships between negative affective states (depression and anxiety), physical/functional status, and emotional well-being during early treatment and later in recovery after orthopaedic trauma injury. Design: This was a secondary observational analysis from a randomized controlled study performed at a Level-1 trauma center. Patients: Patients with orthopaedic trauma (N = 101; 43.5 ± 16.4 years, 40.6% women) were followed from acute care to week 12 postdischarge. Main Outcome Measures: Patient-reported outcomes measurement information system measures of Physical Function, Psychosocial Illness Impact—Positive and Satisfaction with Social Roles and Activities and the Beck Depression Inventory-II and the State-Trait Anxiety Inventory were administered during acute care and at weeks 2, 6, and 12. Secondary measures included hospital length of stay, adverse readmissions, injury severity, and surgery number. Results: At week 12, 20.9% and 35.3% of patients reported moderate-to-severe depression (Beck Depression Inventory-II score ≥20 points) and anxiety (State-Anxiety score ≥40 points), respectively. Depressed patients had greater length of stay, complex injuries, and more readmissions than those without. The study sample improved patient-reported outcomes measurement information system T-scores for Physical Function and Satisfaction with Social Roles and Activities by 40% and 22.8%, respectively ( P < 0.0001), by week 12. Anxiety attenuated improvements in physical function. Both anxiety and depression were associated with lower Psychosocial Illness Impact—Positive scores by week 12. Conclusions: Although significant improvements in patient-reported physical function and satisfaction scores occurred in all patients, patients with depression or anxiety likely require additional psychosocial support and resources during acute care to improve overall physical and emotional recovery after trauma. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.